Phylogenetic relationship and morphological characters of common house gecko Hemidactylus frenatus (Squamata: Gekkonidae) in Nghe An province - Ma Seo Seng; Bui Thuy Linh; Dam Thanh Nga; Bui Van Thang; Ha Bich Hong; Luu Quang Vinh (Journal of Forestry Science and Technology, 2025)
Hemidactylus frenatus Duméril & Bibron (Gekkonidae) is a fairly common species and has a wide distribution from Asia, Americas, Africa, Australia, and a number of tropical islands worldwide. Although this species is distributed from the North to the South in Vietnam, studies on morphological characters and genetic diversity are limited. In this study, we used two mtDNA sequences, Cytb (Cytochrome b) and ND2 (NADH dehydrogenase subunit 2), to evaluate the genetic relationships of five H. frenatus specimens in Nghe An province. The genetic distances between the studied samples were relatively low, 0.3% and 0.1% for Cytb and ND2 sequences, respectively. Phylogenetic analyses based on Cytb and ND2 sequences showed that all five samples were grouped together with H. frenatus on GenBank with significant support (100%). The genetic divergence between the H. frenatus specimens in Nghe An and the H. frenatus specimens on GenBank were also small, ranging from 0.0% to 0.6%, while high genetic distance between the five H. frenatus specimens and othe species in the genus Hemidactylus was observed, ranging from 29% to 46%. In addition, the morphological characters of H. frenatus species in Nghe An are also described to provide additional biological data for studies on genetic relationships and the invasion process of the species.